Water/AOT/IPM/alcohol reverse microemulsions: Influence of salts and nonionic surfactants on structure and percolation behavior - Liu, Jiexiang; Zhang, Xiaoguang; Zhang, Haijiao (The Journal of chemical thermodynamics, 2014)
•Hydrogen bond interactions cause NaSal assist the percolation.•Brij-56 (TX-100) makes Peff decrease and droplets diameter increase, promoting the percolation.•Spans have little effect on percolation due mainly to their small headgroup.•Alcohol can decrease evidently the activation energy by enhancing the interfacial flexibility. Influence of salts (sodium chloride, sodium salicylate and sodium cholate) and nonionic surfactants (Brij-56, TX-100, Span-20, Span-40 and Span-60) on structure and percolation behavior of water/AOT/IPM/propanol (butanol) systems were systematically investigated using conductivity and dynamic light scattering. Percolation behavior had a distinct change with different types of salts and nonionic surfactants. Addition of sodium chloride delayed the conductivity percolation, while sodium salicylate and sodium cholate assisted the percolation. Addition of Brij-56 and TX-100 promoted evidently the conductivity percolation, whereas Spans had little effect. Conductivity behavior was further discussed from the structural properties of nonionic surfactants and salts, and the surfactant packing parameter (P). Droplets sizes were measured using dynamic light scattering to underline the effect of nonionic surfactants on P. Furthermore, lnσ had a linear correlation with temperature in the range of (278.15 to 313.15)K. No percolation threshold induced by temperature was detected among all the studied systems. Moreover, the activation energy for conductivity was also estimated and discussed according to the Arrhenius-type equation.